The relationship between the performance of some offensive and defensive skills, and the results order of teams participating in Olympics London 2012 for men beach volleyball - Mahrous, A. A. K. M. (Assiut Journal of Sport Science and Arts, 2014)
1. This study aims at identifying the relationship between the order of participating teams in the Olympics LONDON 2012 for men beach volleyball and points achieved in the serve skill, 2. Identifying the relationship between the order of participating teams in the Olympics LONDON 2012 for men beach volleyball and points achieved in spiking skill, 3. Identifying the relationship between the order of participating teams in the Olympics LONDON 2012 for men beach volleyball and points achieved in block skill, and 4. Identifying the relationship between the order of participating teams in the Olympics LONDON 2012 for men beach volleyball and Dig skill.